Growth Response and Yield Of Lettuce (Lactuca Sativa L.) On Top Soil Alfisol Planting Media From Jamaimo Village, Mariat District, Sorong Regency To Bio Boost Fertilizer Treatment - Nurul Fajeriana; Muzna Ardin Abdul Gafur; Iskandar Iskandar (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Lettuce has great potential to be developed. However, the limited condition of agricultural land in Indonesia requires alternative for efficient cultivation systems that can maintain the yield and growth of lettuce plants. Therefore, the cultivation carried out in this study was cultivation on narrow land with polybags using planting media top soil Alfisoll from Jamimo Village, Mariat District, Sorong Regency. Considering this, a study was conducted to determine the effect of best concentration of liquid Bioboost organic fertilizer in increasing the growth and yield of lettuce on Alfisol top soil planting media. This research was conducted in Klawuyuk Village, Sorong City, and analyzed soil samples at the Chemistry and Soil Fertility Laboratory, Department of Soil Science, Faculty of Agriculture, Hasanuddin University Makassar. This study used a Completely Randomized Design (CRD) with one treatment factor, namely the concentration of Bio-Boost liquid organic fertilizer which consisted of 4 treatment levels, namely 1) without Bio-Boost liquid organic fertilizer (control)); 2) 60 ml Bio- Boost liquid organic fertilizer + 1 liter of water 3) 80 ml Bio-Boost liquid organic fertilizer + 1 liter of water; 4)100 ml Bio-Boost liquid organic fertilizer + 1 liter of water. Observational data were analyzed statistically with analysis of variance at the 5% level. The dosage of Bio-Boost liquid organic fertilizer gave a very significant effect on the growth and yield of lettuce on Alfisol top soil planting media, where the concentration of B2 treatment (80 ml of Bio-Boost liquid organic fertilizer + 1 liter of water) resulted in variables growth and the highest yield, namely plant height 39.5 cm, several leaves 11, leaf area 91.3 cm, and wet weight 610, 4 gr.